2015
DOI: 10.1103/physreva.91.032707
|View full text |Cite
|
Sign up to set email alerts
|

Kinematically complete study of low-energy electron-impact ionization of neon: Internormalized cross sections in three-dimensional kinematics

Abstract: Low-energy (E0=65eV) electron-impact single ionization of Ne (2p) has been investigated to thoroughly test state-of-the-art theoretical approaches. The experimental data were measured using a reaction microscope, which can cover nearly the entire 4π solid angle for the secondary electron emission energies ranging from 2 to 8 eV, and projectile scattering angles ranging from 8.5 to 20.0. The experimental triple-differential cross sections are internormalized across all measured scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
29
1
Order By: Relevance
“…3), where both OAMO and PA predictions are significantly smaller than that observed experimentally in the angular ranges θ 2 ≤ 90 • and, by symmetry, θ 2 ≥ 270 • . In comparison for ionization of the atomic target Ne, which has the same number of bound electrons as H 2 O, the three-body distorted-wave theory reveals an unprecedented degree of agreement with experiment [13,31]. The two calculations based on the three-body distorted-wave theory differ strongly from each other in both the relative shape and the magnitude of the cross sections.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…3), where both OAMO and PA predictions are significantly smaller than that observed experimentally in the angular ranges θ 2 ≤ 90 • and, by symmetry, θ 2 ≥ 270 • . In comparison for ionization of the atomic target Ne, which has the same number of bound electrons as H 2 O, the three-body distorted-wave theory reveals an unprecedented degree of agreement with experiment [13,31]. The two calculations based on the three-body distorted-wave theory differ strongly from each other in both the relative shape and the magnitude of the cross sections.…”
Section: Discussionmentioning
confidence: 72%
“…Recent calculation of (e, 2e) on CH 4 using the molecular three-body distorted-wave approximation found that the method with proper averages (PA) is in much better agreement with experiment than the orientation-averaged molecular orbitals (OAMO) calculations [27]. On the other hand, experimental techniques were recently developed that allow for simultaneously accessing a large fraction of the entire solid angle and a large range of energies of the continuum electrons in the final state [28,29], the entire angular acceptance for the slow ejected electron within the scattering plane [30] and, more recently, the measurements of internormalized cross sections [13,31,32]. Thus, theories can be tested significantly more comprehensively over a large range of the final state phase space.…”
Section: Introductionmentioning
confidence: 91%
“…Much more challenging, however, is the treatment of more complex targets, such as the heavy noble gases Ne−Xe [5][6][7][8][9][10][11][12][13][14][15]. In recent years, we measured the ionization of Ne(2p) [5,6] and Ar(3p) [7,8]. For Ne(2p), unprecedented agreement between experiment and predictions from a B-spline R-matrix (BSR) with pseudostates approach was obtained first for a projectile energy of 100 eV [5] and most recently also for the even lower energy of 65 eV [6].…”
Section: Introductionmentioning
confidence: 99%
“…It can contain additional processes involving momentum transfer, post-collision interaction, and exchange, which are expected to become more pronounced for low impact energy. 29 The purpose of the present work is to refine our earlier study 20 with the improved conditions for more detailed understanding of the fragmentation processes of CH 4 and to compare the results with photoionization studies.…”
Section: Introductionmentioning
confidence: 99%